Authority Work, Catalogers, and Contemporary Authors: Results of an Online Survey. Issue 3 (2nd July 2020) - Stanishevskaya, Irina
ABSTRACT: The article presents the results of an online survey, which was designed to examine the relationships between catalogers and contemporary authors during the process of establishing authorized access points and creating personal name authority records (NARs) for the purpose of breaking conflicts in the Library of Congress Name Authority File (LC NAF) and/or of obtaining additional identifying attributes. This article may be useful for individuals involved in the creation of personal name authority records.